INCLUSIVE ARCHITECTURE OF OPEN URBAN SPACES IN THE CONTEXT OF URBAN EQUALITY - Vasylyshyn, Vitalii; Itchenko, Dmytro; Gavryk, Olga (Theory and practice of design, 2025)
The relevance of the study is determined by the urgent need to create open urban spaces that comply with the principles of urban equality and ensure barrier-free access for all population groups. In the context of global urbanization and ongoing social transformations, particular importance is attached to rethinking architectural approaches to the organization of public green areas, which are capable of integrating inclusive solutions and fostering social integration. The purpose of the article is to identify the key factors and principles of inclusive architecture of open urban spaces, to develop approaches to overcoming barriers, and to design a conceptual model for transforming green areas based on the principles of urban equality. The research methodology relies on a systemic and interdisciplinary approach, incorporating methods of structural-functional analysis as well as comparative typology of national and international practices. Results. The study established that the formation of inclusive architecture of open urban spaces requires consideration of the socio-demographic characteristics of the population, the spatial and functional parameters of the environment, ecological requirements, and legal standards. The analysis of scholarly sources made it possible to identify the main barriers to accessibility and social isolation, and to develop an algorithm for transforming green areas, which encompasses the stages of user needs assessment, evaluation of the existing environment, identification of barriers, development of solutions, piloting, implementation, and monitoring. Scientific novelty. The article systematizes the principles of inclusive architecture in the context of urban equality and proposes an algorithm for the transformation of urban green areas. Its novelty lies in combining theoretical and methodological approaches with practical urban planning tools, thereby enabling a comprehensive analysis of accessibility and social integration. Barriers and social factors influencing inclusivity are presented in a systematic manner, which provides a solid academic basis for further quantitative assessment of urban inclusiveness. Practical relevance. The proposed algorithm for the transformation of green areas can be applied in strategic urban planning, municipal governance, and the design of open spaces. It serves as a practical guideline for architects and urban planners in creating accessible and barrier-free public environments. The developed approaches contribute to harmonizing spatial development, improving the quality of urban life, and integrating diverse social groups into a shared space-an aspect of particular importance in the processes of post-war recovery and modernization of Ukrainian cities.